Dialetic and tékhnē in Plato’s Cratylus - Brinati Furtado, Daniela (2019)
In this article, we evaluated the notion of tékhnē in three contexts of the Cratylus, which allows us to identify three nuances associated with the term: 1. as a “know how” intermediated by an instrument (388e-389a); 2. as the possession of a noetic knowledge, in the moment of the etymological analysis of this word (414b-c) and 3. as the art of representing things through their names (428a-440e). Our point is to show these meanings not as something disconnected and fragmentary, but that they are developed within the dialectical movement of this dialog itself.